More than just temperature: the effects of nest relocation on incubation environment and hatchling quality in green turtles (Chelonia mydas) - David Dor; David T. Booth; Lisa E. Schwanz (Marine Biology, 2026)
Nest relocation and shading are widely used conservation strategies intended to mitigate threats to marine turtle hatchling survival. However, these interventions may carry unintended fitness costs. Estimating such effects can be challenging, especially in the absence of opportunities to compare with natural, undisturbed nests. Green turtle ( Chelonia mydas ) clutches were assigned to one of three treatments ( in situ , shaded relocation, or unshaded relocation) on Heron Island, Queensland, Australia (23.44307° S, 151.91809° E), during two nesting seasons (Dec 2022 – Feb 2023 and Dec 2023 – Feb 2024). Incubation temperature, hatching and emergence success, sex ratio, morphology (carapace size and body mass), and performance (self-righting ability and crawl speed) were assessed. Relocated unshaded nests exhibited higher incubation temperatures than in situ and shaded nests, especially during the final two weeks of incubation. Consequently, warmer nests produced smaller hatchlings with higher mass relative to size (residual mass) and poorer self-righting performance. Notably, in situ and shaded relocated nests had comparable incubation temperatures, yet still differed in hatching success, hatchling size, and self-righting ability, indicating that relocation can carry developmental consequences independent of those related to thermal averages. These findings highlight the importance of prioritising in situ nesting where feasible and accounting for both thermal and non-thermal factors of relocation sites if relocation is required.

Insights on the heterogeneity of thermal transfer in the chalk aquifer using fibre-optic distributed temperature sensing - Katerina Kyrkou; Joseph Kelly; Adam Booth; Fleur Loveridge; David Boon; Edward Hough; Lawrence Scott; Matthew Jackson; Adrian Butler; Daniel Perez; Athena Chalari (Geothermics, 2026)

Roadless rule rescission threatens highest integrity forest ecosystems in the United States - David J. Mildrexler; Logan T. Berner; Beverly E. Law; Mary S. Booth (Biological Conservation, 2026)

Thermal history and behavioural plasticity shape reef fish tolerance to marine heatwaves - Angus Mitchell; Sean D. Connell; Ben P. Harvey; Sylvain Agostini; Jeffrey Jolly; Guinther Mitushasi; Timothy Ravasi; David J. Booth; Ivan Nagelkerken (Coral Reefs, 2026)
Marine heatwaves are becoming more frequent and intense, driving mass fish mortalities and reshaping marine ecosystems, yet the capacity of fishes to tolerate heatwaves remains unclear. We quantified physiological condition and behavioural responses of juvenile warm-water ( Abudefduf vaigiensis ) and cool-water ( Microcanthus strigatus ) fishes from three natural climate analogues—an ambient temperate reef, an ocean warming analogue, and a combined warming and extreme acidification analogue—before and during the 2023 global marine heatwave, and under a + 3 °C simulated heatwave in the laboratory. In the laboratory, warm-water fish from the warm reef began the experiment in leaner condition than cool reef fish but increased their bite rates under heatwave conditions, compensating for elevated metabolic demand and maintaining body condition. Cool-water fish showed no behavioural adjustment to the heatwave, and body condition diverged by reef origin: cool reef fish lost weight across all treatments while warm- and extreme-origin fish maintained condition, suggesting tolerance was conferred by prior thermal history rather than acute behavioural responses. In the field, warm-water fish were leaner and had lower protein content during the 2023 heatwave than before it, while cool-water fish from the extreme reef had lower body condition than those from the cool reef prior to the heatwave. Our findings suggest that behavioural plasticity can facilitate warm-water fish tolerance to heatwaves at their cold leading edges, while thermal history supports heatwave tolerance in cool-water fish within their core ranges. Populations inhabiting naturally extreme climate analogues may therefore harbour pre-adapted, climate-resilient fish in a future ocean.

Natural maintenance of biofouling on coral nurseries used across the Great Barrier Reef - Gemma M. Gillette; Emma F. Camp; John Edmondson; David J. Booth; Rachael I. Scott; David J. Suggett (Marine Environmental Research, 2026)

A spatial approach to duet function in Adelaide's warbler, Setophaga adelaidae - Samantha W. Krause; Tyler R. Bonnell; Marcus J. Dostie; Samantha I. Booth; Peter C. Mower; David M. Logue (Animal Behaviour, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Fredrick J. Rich (1951–2025): palynologist, coal geologist, naturalist, and teacher - David T. Pocknall; James C. Hower; Robert K. Booth; Jennifer M.K O’Keefe (Palynology, 2026)

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Marine Heatwaves, Ocean Warming and Acidification Reshape Reef Fish Gut Microbiomes - Angus Mitchell; Chloe Hayes; Callum J. Hudson; Sean D. Connell; Ben P. Harvey; Sylvain Agostini; Jeffrey Jolly; Timothy Ravasi; David J. Booth; Ivan Nagelkerken (Molecular Ecology, 2026)
Extreme climatic events and gradual climate change are increasingly anticipated to interact and reshape ecological communities. However, the combined effects of ocean warming, acidification and marine heatwaves on host‐associated microbial communities and their potential role in host adaptation remain poorly understood. Here, we assessed shifts in gut microbiome communities and their associations with physiological performance in one tropical ( Abudefduf vaigiensis ) and one subtropical ( Microcanthus strigatus ) reef fish species, across three temperate reefs representing natural analogues of climate change: a present‐day baseline (‘cool reef’), a chronically warmed reef (‘warm reef’) and a reef experiencing combined warming and extreme acidification (‘extreme reef’). We also examined gut microbiome changes in A. vaigiensis before and during a severe marine heatwave. A. vaigiensis had lower gut microbiome evenness and diversity at the warm (43% and 44% decrease, respectively) and extreme (38% and 31% decrease) reefs compared to the cool reef, and its gut microbiome community shifted at the extreme reef with a 122% increase in abundance of opportunistic bacteria Vibrio . A. vaigiensis also had lower gut microbiome richness at the warm (42% decrease) and extreme (52% decrease) reefs during the heatwave compared to pre‐heatwave individuals. In contrast, M. strigatus showed higher microbiome evenness (99% increase) and diversity (98% increase) at the warm reef compared to the cool reef; however, these gains were lost at the extreme reef, with microbiome diversity and evenness returning to cool reef levels. Microbiome changes in both species were generally not associated with their physiological performance (protein content, oxidative stress, antioxidant capacity or body condition). Our findings suggest that marine heatwaves, ocean warming and acidification can reshape reef fish gut microbiomes, driving simplification in Abudefduf vaigiensis but distinct restructuring in Microcanthus strigatus . We conclude that climate‐driven microbiome reshuffling may alter host–microbiome relationships and functions in fishes in a future ocean.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Range‐extending fish become competitive dominants under ocean warming but not heatwaves or acidification - Angus Mitchell; Ericka O. C. Coni; Sean D. Connell; David J. Booth; Ben P. Harvey; Sylvain Agostini; Timothy Ravasi; Ivan Nagelkerken (Ecology, 2026)
Ocean warming is driving species range extensions into cooler regions. The direct physiological influence of warming on species performance can accelerate such extensions into novel ecosystems; however, indirect effects of invader–resident interactions in cooler regions may counter these positive effects. Here, we examined the foraging performance and densities of competing warm‐water and cool‐water fishes across a latitudinal temperature gradient spanning 1500 km from tropical to temperate reefs subjected to rapid ocean warming in the southern hemisphere, and across natural analogs of temperate, tropicalized, and acidified reef localities in the northern hemisphere, and during a severe marine heatwave at a temperate reef. While current levels of ocean warming have allowed the warm‐water fish to extend their ranges into temperate ecosystems at both hemispheres, their foraging performance was reduced at both the cold‐ and warm‐temperate reefs compared to the (sub)tropical reefs. However, at the (warmer) tropicalized reef, the warm‐water fish had higher foraging performance and maintained densities, even under extreme pH reduction, compared to the temperate reef. In contrast, the cool‐water species struggled at the warmer tropicalized and extreme reefs with reduced foraging performance and lower population densities compared to the temperate reef. Contrastingly, the severe heatwave experienced at the temperate reef did not alter the foraging behaviors of either species. We suggest that ocean warming boosts the foraging performance of the range‐extending warm‐water fish and impairs that of their cool‐water competitor at temperate reefs, irrespective of acidification and heatwaves, leading to a shift in dominance hierarchies on temperate reefs. We conclude that warming‐driven increases in foraging performance of the warm‐water species may alleviate foraging limitations and enhance its establishment at its leading range edges under climate change, to the detriment of its cool‐water competitors.

Skeletal muscle atrophy induced by aging and disuse atrophy are strongly associated with the upregulation of the endoplasmic stress protein CHOP in rats - J. Max Michel; Joshua S. Godwin; Nathan R. Kerr; Thomas E. Childs; Frank W. Booth; C. Brooks Mobley; David C. Hughes; Michael D. Roberts (Molecular Biology Reports, 2025)
Background While canonical anabolic and proteolytic pathways have been well examined in the context of skeletal muscle proteostasis, the roles of endoplasmic reticulum stress (ERS) and the induced unfolded protein response (UPR) are underappreciated. Thus, we aimed to determine whether aging and/or disuse atrophy in rats altered skeletal muscle ERS/UPR markers. Methods and Results Soleus (SOL) and plantaris (PLT) muscles of 3-month-old (mo), 6 mo, 12 mo, 18 mo, and 24 mo rats (9–10 per group, 48 in total) were analyzed for UPR proteins with further analysis performed on the protein CHOP. The gastrocnemius muscles of 4 mo rats that had undergone hindlimb immobilization (HLI, n = 12) or sham casting (CTL, n = 12) were analyzed for similar targets as well as more extensive CHOP-related targets. CHOP protein was greater in the PLT and SOL of 18 and 24 mo rats versus other age groups ( P < 0.05). Moreover, negative correlations existed between CHOP expression and normalized PLT ( R =-0.702, P < 0.001) and SOL ( R =-0.658, P < 0.001) muscle weights in all rats analyzed at different ages. CHOP protein expression was also greater in the gastrocnemius of HLI versus CTL rats ( P < 0.001), and a negative correlation existed between CHOP protein expression and normalized muscle weights in these rats ( R =-0.814, P < 0.001). Nuclear CHOP protein levels ( P < 0.010) and genes transcriptionally regulated by CHOP were also greater in HLI versus CTL rats ( P < 0.001) implicating transcriptional activity of CHOP is elevated during disuse atrophy. Conclusions CHOP is operative during aging- and disuse-induced skeletal muscle atrophy in rodents, and more research is needed to determine if CHOP is a key mechanistic driver of these processes.

The impact of sea level rise on nesting sea turtles: a global meta-analysis to highlight current understanding and knowledge gaps - Melissa N. Staines; David T. Booth; Jacques-Olivier Laloë; Graeme C. Hays (Marine Biology, 2025)
Sea turtles face a number of threats from climate change. One pertinent threat is the impact of sea level rise (SLR), which can lead to a loss of nesting habitat and reduced survival of embryos due to inundation and erosion. Here we review the impacts of SLR on sea turtles. We examined 34 studies (66 assessments) on SLR impacts across six species and 40 sites globally, with 62.1% of assessments located in the Americas. Overall, 78.8% of the assessments showed declining trends in historical and projected estimates of nesting habitat area and or nest survival from inundation. Assessments with projected nesting habitat area showed appreciable loss across all site types (coral island, elevated island, barrier island and mainland), regardless of the SLR scenario. The projected percentage of habitat loss and nest flooding was greatest in island sites compared to the mainland sites, highlighting that SLR is likely to be most acute for low-lying islands with no nearby alternative nesting areas. We reviewed the predicted extent of nesting beach loss and examined how natural processes and conservation interventions might mitigate this threat. However, we require more empirical data on the extent of historical nesting habitat loss. There is also little known about a population’s ability to colonise new nesting areas once a site becomes unsuitable. By tracking their routes towards the breeding sites, there is potential to show how resilient sea turtles are to environmental change, as females may be exposed to other suitable nesting sites on their migration route.

Improving conservation outcomes for seadragons: data, knowledge gaps, and future directions - Chrissy A. Tustison; Nerida G. Wilson; Greg W. Rouse; David J. Booth; Maarten De Brauwer (Reviews in Fish Biology and Fisheries, 2025)
Seadragons are charismatic fishes endemic to Australia’s Great Southern Reef and are flagships for marine biodiversity. Due to their unique appearances and behaviors, seadragons are of interest for both scientific research and broader conservation purposes. However, studies on wild seadragon populations are challenging to implement, and peer-reviewed data on population demographics, life histories, and other aspects of seadragon biology and ecology are currently limited. Seadragon habitats, including kelp-covered reefs and seagrass meadows, have declined in various areas of the southern Australian coast, spurring concerns that seadragon abundances may also be contracting. The lack of range-wide baseline data on seadragon populations has precluded a robust understanding of their vulnerability to extinction, and further conservation-focused research has been recommended by past studies. Here, we summarize existing research on the three known seadragon species: common, leafy, and ruby seadragons, with the aim of improving future conservation outcomes for seadragons. Range-wide population size estimates and trends in abundance data are key knowledge gaps preventing accurate extinction risk assessments. Lack of data about basic ecological and biological factors such as longevity and reproduction further hinder effective conservation actions. We describe developing research methodologies including citizen science, machine learning, habitat mapping, and molecular methods that show promise for improving outcomes for these iconic fishes and the habitats they rely on.

Patterns and drivers of movement in the estuary-associated sparid Acanthopagrus australis from a large-scale tagging study - Holly Gunton; Ashley M. Fowler; David J. Booth; John Stewart (Fisheries Research, 2025)

Mass stranding of common (weedy) seadragons ( Phyllopteryx taeniolatus ) in Sydney : impacts and implications - David J. Booth; Andrew Trevor‐Jones; Selma Klanten; Giglia A. Beretta (Journal of Fish Biology, 2025)
In April 2022, mass stranding of weedy (common) seadragons occurred, with a total of over 200 individuals washed ashore on beaches in the Sydney, Australia region, recorded by citizens. Causes of the stranding, which is unprecedented, were likely related to a series of east coast low storm events, leading to record wave heights, record coastal rainfall, and potential loss of critical food sources (schooling mysid crustaceans). A significant proportion of the local population was likely lost in this series of events, indicating a future threat to seadragons, with east coast low intensity predicted to increase under human‐caused climate change.

Chemical emissions from offshore wind farms: From identification to challenges in impact assessment and regulation - Elena Hengstmann; Pablo Zapata Corella; Katharina Alter; Maria J. Belzunce-Segarra; Andy M. Booth; Javier Castro-Jiménez; Niklas Czerner; Karien De Cauwer; Geneviève Deviller; Alessio Gomiero; Nils Goseberg; Simone Hasenbein; et al. (Marine Pollution Bulletin, 2025)

Efficacy of unbaited and baited green multi-funnel traps for detection of Agrilus species and other wood-boring beetle taxa - Giacomo Santoiemma; Jon Sweeney; Everett G. Booth; Giacomo Cavaletto; Gianfranco Curletti; Sarah M. Devine; Joseph A. Francese; Emily K. L. Franzen; Filippo Giannone; Mischa Giasson; Jerzy M. Gutowski; Cory Hughes; et al. (Journal of Pest Science, 2025)
Semiochemical-baited traps are a key component of post-border surveillance for detection of non-native and potentially invasive bark and wood-boring beetles (Buprestidae, Cerambycidae, Curculionidae: Scolytinae) at risk of introduction in untreated woody materials used in global trade. Because the particular species that may arrive with imported goods is unknown, plant protection agencies need trapping protocols that effectively survey all three taxa. Baiting traps with host volatiles and aggregation/sex pheromones of longhorn beetles increases efficacy of detecting Cerambycidae and Scolytinae, but its effect on detection of Agrilus species and other jewel beetles is unknown. In this multi-country trapping study we found that the addition of ethanol and common aggregation/sex pheromones of longhorn beetles to green multi-funnel traps placed in the mid-upper forest canopy had negative effects on abundance of Agrilus species and other jewel beetles collected but no effect on their species richness, and significant positive effects on species richness and abundance of Cerambycidae and Scolytinae. Baiting green canopy traps with longhorn beetle pheromones increased the efficacy of traps for detecting total target taxa of bark and wood-boring beetles at risk of international movement in untreated woody materials. This information is beneficial for the design of multi-taxa surveys, potentially saving money and resources without decreasing trapping efficacy.

Global Decline in the Size of Sea Turtles - Graeme C. Hays; Mohd Uzair Rusli; David Booth; Jacques‐Olivier Laloë (Global Change Biology, 2025)
Changes in mean adult body size may be a universal response to global warming and sometimes lead to conservation concerns. We show that size reductions in sea turtles are now the norm and have another explanation. From 18,707 measurements of nester size (curve carapace length) for sea turtles spanning 30 years from Redang Island (Malaysia), where nearly all nesting individuals have been tagged, we show that the mean size was initially fairly stable and then decreased by 4.0 cm from 100.8 cm in 2005 to 96.8 cm in 2022, which likely translates to a change in mean mass from 120 to 105 kg. At the same time, nesting increased from around 300 to 2000 nests per year. Consistent with this finding of a size reduction in an expanding population, at 27 of 31 sites across the globe where changes in the mean size of nesting sea turtles have been assessed, mean size is decreasing, and the most marked decreases are at sites where population size is increasing most dramatically. Taken together, these focal and global findings suggest that an important driver of size reductions in sea turtles is an influx of small first‐time nesters (neophytes) in expanding populations, and hence, size reductions are partially a consequence of successful sea turtle conservation measures and population recoveries. At the same time, the focal observations in Malaysia show that the mean size of neophytes has also been getting smaller over time: from 99.6 to 96.8 cm between 2005 and 2022, likely because of a change in foraging environments. While smaller turtles have lower reproductive output, this negative consequence of decreases in nester size will often be more than offset by increases in nesting numbers that are occurring widely.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Early life history traits and elevated growth trajectories associated with survival into winter in range-expanding coral reef fish - Alexander L. Rigg; Ashley M. Fowler; Brigitte Sommer; David J. Booth (Marine Biology, 2025)
Climate change is driving the poleward range expansion of sub-tropical and tropical marine species into temperate ecosystems, with ocean-warming hotspots experiencing rapid shifts in species distributions. While recruitment to temperate waters by expatriating tropical vagrant fish is increasing, surviving through the cooler winters remains a significant barrier to their establishment. This study investigates the links between early life history traits and survival into winter in the Sergeant Major ( Abudefduf vaigiensis ), a tropical damselfish expanding its range into temperate southeastern Australia. Using otolith microstructure analysis, we reconstructed the early life histories of 122 individuals collected from rocky reefs in Sydney (33.8 o S) Australia in 2022 and 2023 and assessed their early life history traits. Our results demonstrate that individuals sampled during winter (hereafter “wintered fish”) had a larger size at hatching, longer pelagic larval duration, and higher body condition than fish collected before winter. Lower settlement water temperatures were positively associated with winter survival, indicating that a settlement date closer to the onset of winter was favourable. Additionally, wintered fish, exhibited higher growth rates in early life compared to fish sampled prior to winter onset. These findings suggest that some early life history traits are selected for survival into winter, potentially mediating the physiological impacts of declining water temperature. If such traits increase overwinter survival they may facilitate the establishment of this range-expanding species in temperate rocky reef environments.

Faster larval growth and shorter pelagic duration enhance the post-settlement persistence of a common range-extending coral-reef fish in a temperate ecosystem - Alexander L. Rigg; Ashley M. Fowler; Ivan Nagelkerken; David J. Booth (Coral Reefs, 2025)
Climate-induced ocean warming facilitates the poleward range expansion of tropical marine species into temperate waters. Such tropicalisation is reshaping marine ecosystems globally and has ecological implications. Our understanding of the factors influencing the establishment and persistence of vagrant tropical species in temperate waters remains limited. To address this knowledge gap, we examined which early life history traits affect the post-settlement persistence of a vagrant tropical fish, the sergeant major damselfish Abudefduf vaigiensis , in temperate waters off southeast Australia. Over an 8-week period, fish were collected, and otolith microstructure analysis indicated that early post-settlement persistence was linked to fast larval growth in the week prior to settlement and to shorter pelagic larval duration, but not body size at hatching or body size at settlement. We conclude that successful invasions of temperate ecosystems by this vagrant tropical fish is likely mediated by demographic advantages these fish gain as early-stage larvae.

Otolith and Genomic Data Reveal Temporal Insights Into Stocking Across a Large River Basin in a Mobile, Long‐Lived Australian Freshwater Fish Species - Katherine A. Harrisson; Luciano B. Beheregaray; Christopher M. Bice; Emily J. Booth; Chris J. Brauer; Gavin L. Butler; David Dawson; Olga Dudchenko; Benjamin G. Fanson; Graeme Hackett; Annique Harris; Matthew J. Jones; et al. (Molecular Ecology, 2025)
Freshwater ecosystems and their biota are under increasing pressure from anthropogenic stressors. In response to declining fish stocks, hatchery and stocking programmes are widely implemented as core components of restoration and management strategies, with positive outcomes for some wild populations. Despite this, stocking remains contentious due to potential genetic and ecological risks to wild populations. Monitoring and evaluation of stocking outcomes are critical to ensuring the long‐term sustainability of wild populations, but identification of stocked individuals post‐release remains a key challenge, particularly for mobile species. In this study, we combined otolith (natal origin and age) and genomic data to identify stocked individuals and evaluate the genetic implications of stocking for a culturally and socioeconomically important and mobile freshwater fish, golden perch Macquaria ambigua (family: Percichthyidae), across Australia's Murray–Darling Basin (MDB). We also generated a chromosome‐level genome assembly. Many close kin were detected across the MDB, increasing in prevalence over recent decades and mostly of hatchery origin. Rivers with many close kin were associated with low effective population sizes ( N e

Stomach Microbiome Simplification of a Coral Reef Fish at Its Novel Cold‐Range Edge Under Climate Change - Chloe Hayes; Angus Mitchell; Roger Huerlimann; Jeffrey Jolly; Chengze Li; David J. Booth; Timothy Ravasi; Ivan Nagelkerken (Molecular Ecology, 2025)
Climate‐driven range extensions of animals into higher latitudes are often facilitated by phenotypic plasticity. Modifications to habitat preference, behaviour and diet can increase the persistence of range‐extending species in novel high‐latitude ecosystems. These strategies may be influenced by changes in their gut and stomach microbial communities that are critical to host fitness and potentially adaptive plasticity. Yet, it remains unknown if the gut and stomach microbiome of range‐extending species is plastic in their novel ranges to help facilitate these modifications. Here, we categorised stomach microbiome communities of a prevalent range‐extending coral reef fish along a 2000‐km latitudinal gradient in a global warming hotspot, extending from their tropical core range to their temperate cold range edge. At their cold range edge, the coral reef fish's stomach microbiome showed a 59% decrease in bacterial diversity and a 164% increase in the relative abundance of opportunistic bacteria ( Vibrio ) compared to their core range. Microbiome diversity was unaffected by fish body size, water temperature, physiology (cellular defence and damage) and habitat type (turf, barren, oyster, kelp and coral) across their range. The observed shifts in microbiome composition suggest dysbiosis and low plasticity of tropical range‐extending fishes to novel environmental conditions (e.g., temperate prey and lower seawater temperature) at their novel range edges, which may increase their susceptibility to disease in temperate ecosystems. We conclude that fishes extending their ranges to higher latitudes under ocean warming can experience a simplification (i.e., reduced diversity) of their stomach microbiome, which could restrict their current rate of range extensions or establishment in temperate ecosystems.

How much seagrass does a dugong need? Metabolic rate of live wild dugongs, Dugong dugon , determined through indirect calorimetry (oxygen consumption) - Janet M. Lanyon; Helen L. Sneath; Trevor Long; Wendy H. Blanshard; Graham A. J. Worthy; David T. Booth (Marine Mammal Science, 2025)
Deterioration of seagrass beds worldwide has raised concern about the future of dugongs because almost all aspects of their life history depend on availability of seagrass. Understanding their energy metabolism and consequently how much seagrass they need will inform protective conservation strategies for dugongs. This study determined resting metabolic rate (RMR) in five wild‐caught adult dugongs by measuring oxygen consumption (O 2 ). Measurement conditions met assumptions for RMR, except that dugongs were not postabsorptive, thus a postprandial (pp) allometric equation for herbivorous mammals of similar size was used to predict an expected RMR pp for dugongs of known mass. O 2 was measured for 30 min in a metabolic tank after brief habituation. Dugongs' RMR pp was approximately half that predicted for their body mass but was higher than for manatees. Based on dugongs' RMR pp and considering plant caloric and water content, the daily minimum intake of fresh weight seagrass was 40–65 kg Halophila ovalis , or 20–40 kg Halodule spp. Greater seagrass intake would be required for growing and reproducing dugongs. Slow growth and protracted reproductive rates of dugongs are likely related to limitations in seagrass energy and nutrients. To ensure viability of this vulnerable species, it is critically important to conserve extensive healthy seagrass beds.

Ontogenetic change in body shape for white sharks, Carcharodon carcharias , in Australian waters - Emily Hunt; Russell W. Bradford; David J. Booth; Cameron Doak; Toby A. Patterson; Victor M. Peddemors (Journal of Fish Biology, 2025)
The analysis of how biological shape changes across ontogeny can provide us with valuable information on how species adapt behaviorally, physiologically, and ecologically. The white shark Carcharodon carcharias is one of the largest and most widely distributed apex predators globally, yet an understanding of ontogenetic changes in body shape and relative scaling of length and weight measures is limited, especially in relation to foraging ecology. Through analysis of a suite of shape‐related metrics, we identified ontogenetic patterns of scaling throughout development. Isometric growth was exhibited for most metrics, failing to show a significant deviation from an isometric slope of 1.0 for length–length relationships, and 3.0 for weight–length relationships. The most notable difference from this trend was the negative allometric growth observed for the upper caudal‐fin lobe length, trunk length, and the mouth length. The surface area of the fins also presented a strong, positive relationship with precaudal length (PCL) and the girth at the pectoral fin. Negative allometric growth was exhibited for three of the fins (pectoral, upper caudal fin, and lower caudal fin) against PCL, exhibiting a significant deviation from the expected isometric growth of 2.0 for area–length relationships. There were no significant differences in morphometric relationships between geographic regions within Australia that samples were collected from. No differences between the sexes were identified; however, this may be an artifact of the lack of mature animal samples. Conversely, life stage was found to have a significant effect on the girth–length and weight–length relationships. The development of regression equations for morphometric measures allows the assessment of white shark body condition and may serve as an assessment tool to understand the potential impacts of human‐induced environmental change on white sharks.

Physiological Traits for Predicting Poleward Extensions in Tropical Fishes: From Lab to Management - Adam T. Downie; Curtis Champion; David J. Booth (Global Change Biology, 2025)
Tropicalization, the phenomena by which tropical organisms are extending their distributions poleward into temperate latitudes in response to increasing temperatures and strengthening boundary currents, is occurring globally. Vagrant tropical species have large ecological and economic ramifications for the temperate habitats they invade. However, not all vagrants are able to persist long term in temperate habitats, with the first winter being a potential bottleneck for their persistence. This brings into question how some tropical vagrant species are successful at surviving temperate conditions and the physiology underpinning this success. This provides the opportunity to not only look at the available data introspectively but also forward‐thinking by applying a range of holistic physiological traits relevant for biology and management. Therefore, the aim of our review is twofold: to review the current state‐of‐knowledge of the physiological mechanisms underpinning tropicalization and to develop a physiological framework by which current practices can complement new perspectives and tools. We use range‐expanding tropical reef fishes as a model group of over 100 species undergoing climate‐driven range shifts and eastern Australia as a case‐study location due to it being a primary focal “living laboratory” for understanding tropicalization dynamics since the early 2000s. Current studies suggest that diet, behavior, and metabolic trade‐offs may explain vagrant fish persistence, but these studies focus on whole‐animal traits. Our framework helps expand upon focal traits, life stages, experimental design, physiological traits (e.g., we highlight the value of genetic and cellular markers for metabolic pathway changes under cold stress as potential biomarkers) and species to improve our understanding of the mechanisms underpinning tropicalization. Taken together, our framework places emphasis on measuring a suite of complimentary physiological traits, from cellular to whole‐animal, to help guide future predictions of the long‐term persistence of tropical species in temperate habitats.

Overwintering performance of three juvenile temperate estuarine fishes - Clara Bellotto; Ashley M. Fowler; David J. Booth (Journal of Experimental Marine Biology and Ecology, 2025)

Efficacy, non-target impacts, and costs of mechanical control options against a bioturbator in bivalve aquaculture - Jennifer L. Ruesink; C. Haleh Mawson; Brian Allen; Jeffrey Barrett; David Beugli; Steven Booth; Laura Butler; Bill Dewey; Cinde R. Donoghue; Brett R. Dumbauld; Kristine Feldman; Zachary Forster; et al. (Aquaculture, 2025)

Ocean warming and novel species interactions boost growth and persistence of range‐extending tropical fishes but challenge that of sympatric temperate species in temperate waters - Minami Sasaki; Cristián J. Monaco; David J. Booth; Ivan Nagelkerken (Journal of Biogeography, 2024)
Aim Climate change can have a broad range of impacts on the physiology and behaviour of animals. These effects can be mediated by the presence of other species in the community, but current forecasts of species responses to climate change largely ignore biological interactions. This is particularly true for novel interactions between range‐extending and native species, as this is often considered as noise and excluded from predictive models. Here we simulate how a tropical range‐extending and a local temperate fish species respond to the independent and combined effects of future ocean warming (RCPs 4.5 and 8.5) and novel ecological interactions in temperate ecosystems. Location East coast of Australia, along a ~ 2,000 km latitudinal gradient in a global climate warming hotspot. Taxon Abudefduf vaigiensis (tropical) and Atypicthys strigatus (temperate) fishes. Methods We use a dynamic energy budget model to simulate the length growth (i.e., increases in body length of individuals over time) and population persistence of juveniles of a tropical and a temperate fish species that form mixed‐species shoals, under different climate scenarios with and without the effects of novel ecological interactions. Results Our model forecasts that length growth of the juvenile tropical species will increase under ocean warming across subtropical to temperate regions. This increased length growth will be more drastic in temperate regions than in the subtropics, as winter warming will allow the tropical species to overwinter more frequently and show positive growth throughout the year. In contrast, warmer summer temperatures in the subtropics will likely exceed the optimal temperature of the juvenile temperate species at their trailing edge, resulting in reduced length growth under climate warming. Novel species interactions increased length growth of the juvenile tropical species but did not affect its winter or summer survival. In contrast, novel species interactions with tropical species were forecast to reduce length growth of the juvenile temperate species. Main Conclusions Our study suggests that for some coastal fish species future warming will likely reverse body size dominance between temperate and tropical fish species, with increased novel interactions in temperate ecosystems (due to range extensions) but decreased novel interactions in the subtropics (due to range contractions). Novel species interactions and warming effects on body size and species survival are likely to reshuffle temperate fish communities and their competitive interactions.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Individual performance niches and responses to winter temperature change in three estuarine fishes from eastern Australia - Clara Bellotto; Ashley M. Fowler; David J. Booth (Marine Biology, 2024)
Climate change may impact individual organisms in different ways, a consideration often overshadowed by predominant focus on population effects in studies. We examined three estuarine fish species to determine if individual fish performance, persisted across winter water temperatures. Fish performance at 16 °C (current Sydney winter estuarine water temperature) and 20 °C (predicted under climate change) with low and high food regimes was assessed using key physiological (growth, aerobic scope, burst speed) and behavioural parameters (foraging activity, boldness, shelter usage, predator escape response). We expected a strong positive relationship between performance at 16 °C and 20 °C for each parameter, and interactions with food level, however in general this was not found for any species. Relative performance was only maintained across temperatures for a few parameters, such as bite rate, boldness, and shelter response in one species (trumpeter Pelates sexlineatu s), with aerobic scope in silver biddy Gerres subfasciatus , and boldness in fortescue Centropogon australis . Our results suggest that individuals’ fitness (directly via changes in growth, indirectly via behaviours) might be impacted by climate warming due to differences in relative performance among juvenile individuals across water temperatures. Changes in relative performance among individuals may initially compensate for a population-level response, thereby buffering the effects of climate change.

Efficacy of trapping protocols for Agrilus jewel beetles: a multi-country assessment - Giacomo Santoiemma; David Williams; Everett G. Booth; Giacomo Cavaletto; James Connell; Gianfranco Curletti; Maarten de Groot; Sarah M. Devine; Abigail Enston; Joseph A. Francese; Emily K. L. Franzen; Mischa Giasson; et al. (Journal of Pest Science, 2024)
The genus Agrilus is one of the most diverse insect genera worldwide. The larval feeding activity causes extensive damage in both forests and orchards. In addition, more than 30 species have been introduced outside their native range so far, including the emerald ash borer Agrilus planipennis Fairmaire. Thus, the availability of efficient trapping protocols for early detection of Agrilus species at entry points is of utmost importance. In this study we tested whether trapping protocols developed for surveillance of A. planipennis in North America were also effective for other Agrilus species. In particular, through a multi-country assessment we compared the efficacy of detecting Agrilus species on: (i) green glue-coated prism traps vs. green Fluon-coated multi-funnel traps when baited with the green leaf volatile ( Z )-3-hexenol or left unbaited; and (ii) green multi-panel traps vs. green multi-panel traps baited with dead adult Agrilus beetles (decoys). A total of 23,481 individuals from 45 Agrilus species were caught. Trap design significantly affected both species richness and abundance of Agrilus species in several of the countries where the trapping experiments were carried out, and green prism traps outperformed green multi-funnel traps in most cases. On the contrary, the addition of a ( Z )-3-hexenol lure or dead adult beetle decoys on to traps did not improve trap catches. Our study highlights that reliable trap models to survey Agrilus species are already available, but also that there is the clear need to further investigate chemical ecology of Agrilus species to develop semiochemical lures that can improve detection efficacy.

Predator-avoidance behaviour of target and non-target temperate reef fishes is lower in areas protected from fishing - David A. Feary; Ashley M. Fowler; David J. Booth (Marine Biology, 2024)
The effects of hunting on predator-avoidance behaviour are increasingly being recognised on land but have received less attention in marine systems. We examined whether predator-avoidance behaviour of temperate reef fishes differed between areas protected and not protected from recreational fishing by examining the flight-initiation distance (FID; the distance a predator can approach before the prey animal flees) of six common species in southeastern Australia. By testing species that ranged in desirability to recreational fishers, we could determine if behavioural differences were specific to target species or extended more broadly throughout the assemblage. After accounting for potential variability among sites within protection levels, we found that the FID of all species was higher in fished areas than protected areas, with FID up to 2.4 times higher in fished areas. The two commonly targeted species had the greatest FID response to fishing. FID also increased with body size for all but one species. Our findings indicate the potential for assemblage-wide effects of fishing on predator-avoidance behaviour and are consistent with an indirect mechanism of behavioural modification.

Staining protocols affect use of otolith to estimate the demography of the damselfish sergeant major ( Abudefduf vaigiensis ) - Alexander L. Rigg; Clara Bellotto; Ashley M. Fowler; David J. Booth (Journal of Fish Biology, 2024)
This study assessed the otolith (sagittae, lapilli, and asterisci) increment deposition rate in the range‐shifting damselfish, A. vaigiensis , using different concentrations of Alizain Red S and evaluated the impact of staining on increment width. Daily increment deposition was verified in all otolith types and presented clearer fluorescent markings in the lapilli and sagittae than the asterisci, with high stain concentration showing the best clarity. Higher stain concentrations were found to decrease increment width, suggesting care is needed when using stained otoliths as a proxy for growth for this species.

Novel ecological interactions alter physiological responses of range-extending tropical and local temperate fishes under ocean warming - Minami Sasaki; Angus Mitchell; David J. Booth; Ivan Nagelkerken (Science of The Total Environment, 2024)

Correction to: Projected ocean acidification and seasonal temperature alter the behaviour and growth of a range extending tropical fish - Angus Mitchell; Chloe Hayes; David J. Booth; Ivan Nagelkerken (Coral Reefs, 2024)

Subtropical coral expansion into SE Australia: a haven for both temperate and expatriating tropical reef fishes - Max J. O’Connell; Ashley M. Fowler; Sam J. Allan; Giglia A. Beretta; David J. Booth (Coral Reefs, 2023)
We examined reef fish assemblages in and adjacent to a newly established coral bed (subtropical Pocillopora aliciae ) in temperate south-eastern Australia, to understand whether novel coral habitat is facilitating assemblages of range-expanding tropical and local temperate fishes. This is the first comprehensive assessment of fish species associating with this novel coral habitat within a temperate environment. Twenty fish species were observed associating with the coral (8 tropical and 12 temperate). Both temperate and tropical species were observed at greater (up to 48 times higher) densities on the coral than on nearby temperate rocky reef in the area, suggesting that the corals generally concentrate fish and may aid in tropicalisation for species that use subtropical coral as habitat. Future research should investigate the ongoing expansion of this coral, the relative quality of coral habitat for fish in temperate regions and the potential implications for functioning of temperate rocky reef ecosystems.

Short‐term resilience to climate‐induced temperature increases for equatorial sea turtle populations - Melissa N. Staines; Hayley Versace; Jacques‐Olivier Laloë; Caitlin E. Smith; Christine A. Madden Hof; David T. Booth; Ian R. Tibbetts; Graeme C. Hays (Global Change Biology, 2023)
Projection models are being increasingly used to manage threatened taxa by estimating their responses to climate change. Sea turtles are particularly susceptible to climate change as they have temperature‐dependent sex determination and increased sand temperatures on nesting beaches could result in the ‘feminisation’ of hatchling sex ratios for some populations. This study modelled likely long‐term trends in sand temperatures and hatchling sex ratios at an equatorial nesting site for endangered green turtles ( Chelonia mydas ) and critically endangered hawksbill turtles ( Eretmochelys imbricata ). A total of 1078 days of sand temperature data were collected from 28 logger deployments at nest depth between 2018 and 2022 in Papua New Guinea (PNG). Long‐term trends in sand temperature were generated from a model using air temperature as an environmental proxy. The influence of rainfall and seasonal variation on sand temperature was also investigated. Between 1960 and 2019, we estimated that sand temperature increased by ~0.6°C and the average hatchling sex ratio was relatively balanced (46.2% female, SD = 10.7). No trends were observed in historical rainfall anomalies and projections indicated no further changes to rainfall until 2100. Therefore, the sex ratio models were unlikely to be influenced by changing rainfall patterns. A relatively balanced sex ratio such as this is starkly different to the extremely female‐skewed hatchling sex ratio (>99% female) reported for another Coral Sea nesting site, Raine Island (~850 km West). This PNG nesting site is likely rare in the global context, as it is less threatened by climate‐induced feminisation. Although there is no current need for ‘cooling’ interventions, the mean projected sex ratios for 2020–2100 were estimated 76%–87% female, so future interventions may be required to increase male production. Our use of long‐term sand temperature and rainfall trends has advanced our understanding of climate change impacts on sea turtles.

Exploring contaminants as a disruptor of temperature-dependent sex determination in sea turtle hatchlings - Arthur D. Barraza; Larissa Young; Caitlin E. Smith; David T. Booth; Christine A. Madden Hof; Kimberly A. Finlayson; Frederic D. L. Leusch; Jason P. van de Merwe (Frontiers in Marine Science, 2023)
Sea turtle nesting beaches are experiencing increased sand temperatures as climate change progresses. In one major green turtle ( Chelonia mydas ) nesting beach in the northern Great Barrier Reef, over 99 percent of hatchlings are female. The effects of contaminants on sea turtle hatchling sex determination are not often explored. Liver samples were collected from green turtle hatchlings that were sacrificed for histological sex determination in a parallel study on the effects of sand cooling on sex ratios, and analysed for trace elements via acid digestion and organic contaminants via in vitro cytotoxicity bioassays. Chromium, antimony, barium, and cadmium have previously been demonstrated to be estrogenic, and concentrations of these elements were used to calculate three estrogenic indexes for each clutch: predicted relative estrogenic potency (PEEQA), the sum of percent trace elements above the median of all samples (TEOM), and the sum of percent estrogenic elements above the median of all samples (EstroEOM). Excluding an outlier clutch, cadmium, antimony, and EstroEOM had significant positive relationships with sex ratio deviation. Mean clutch cobalt, lead, antimony and barium, also had a significant positive relationship with clutch sex ratio. There was no relationship between in vitro cytotoxicity of liver extracts and sex ratio, however, 9% of hatchlings had organic contaminants high enough to suggest potential cellular damage. Contaminant effects on sex determination are likely to be caused by a mixture of contaminant interactions as well as temperature. Many trace elements detected in this study have also been linked to negative health effects on hatchlings in previous studies. Considering the risks of feminization due to climate change and potential contaminant effects on hatchling health and sex determination, future studies exploring contaminant effects on sea turtle hatchling sex determination are recommended.

The utility of otolith-based methods for discriminating stock structure of the fishery important monacanthid, Nelusetta ayraud, over an intermediate scale - Holly Gunton; Ashley M. Fowler; Marcus E. Miller; David J. Booth; John Stewart (Fisheries Research, 2023)

Projected ocean acidification and seasonal temperature alter the behaviour and growth of a range extending tropical fish - Angus Mitchell; Chloe Hayes; David J. Booth; Ivan Nagelkerken (Coral Reefs, 2023)
Climate-driven invasions of ecosystems by range-extending animals are often mediated by behavioural modifications that increase their chances of establishment in foreign biological communities. This creates novel ecological interactions that can affect the behaviour of native species in recipient ecosystems. However, this question has seldom been addressed in marine systems, in particular with the additive effect of ocean acidification and the mediating effects of seasonal climate variability. Here, we performed a laboratory experiment to evaluate how novel species interactions, ocean acidification, and projected future summer versus winter temperatures could affect the behaviour and growth of a range-extending tropical and co-shoaling temperate fish. Compared to current-day summer temperatures, tropical fish became 4% more active, 90% more aggressive, and increased their growth rates (standard length: +42%) during future summers in their novel poleward ranges, but reduced their aggression by 64%, boldness by 52%, feeding by 45% and growth rates (wet weight: −70%, standard length: −26%) during future winters compared to current-day summer temperatures. Additionally, tropical fish became 3% more active under ocean acidification compared to no ocean acidification. Conversely, temperate fish behaviour was unaffected by climate treatments but their growth rates were > 200% faster under future winter versus current and future summer temperatures. We conclude that projected future winter conditions in temperate ecosystems may reduce the performance of range-extending fishes in temperate fish communities and slow down tropicalisation of higher latitudes.

Future shock: Ocean acidification and seasonal water temperatures alter the physiology of competing temperate and coral reef fishes - Angus Mitchell; Chloe Hayes; David J. Booth; Ivan Nagelkerken (Science of The Total Environment, 2023)

The impact of graphic design on attention capture and behavior among outdoor recreationists: Results from an exploratory persuasive signage experiment - William L. Rice; Jeremy Shellhorn; Victoria Bloomgren; Lily Booth; Sarah Duncan; Jazzelle Elias; Keaton Flowers; Isabella Gambini; Abigail Gans; Adri Medina; David Obadare; Connor O'Neill; et al. (Journal of Outdoor Recreation and Tourism, 2023)

Mechanism of nanoplastics capture by jellyfish mucin and its potential as a sustainable water treatment technology - Eric A. Ben-David; Maryana Habibi; Elias Haddad; Marei Sammar; Dror L. Angel; Hila Dror; Haim Lahovitski; Andy M. Booth; Isam Sabbah (Science of The Total Environment, 2023)

Operational sex ratio estimated from drone surveys for a species threatened by climate warming - Melissa N. Staines; Caitlin E. Smith; Christine A. Madden Hof; David T. Booth; Ian R. Tibbetts; Graeme C. Hays (Marine Biology, 2022)
Rising sand temperatures resulting from climate warming may cause the ‘feminization’ of sea turtle populations, which have temperature-dependent sex determination. In July and October 2021, we conducted surveys using a drone (also referred to as an unmanned aerial vehicle or UAV) and shore-based observations to assess the operational sex ratio (OSR) (number of males and females in breeding condition) for green turtles ( Chelonia mydas ) in the southern Great Barrier Reef, Australia (23.44 °S, 151.92 °E). Using drone-imagery, the length:width (L:W) ratio of a turtle’s head was used to distinguish loggerhead turtles ( Caretta caretta ) from green turtles, and the L:W of the carapace was used to distinguish juveniles from adult-sized green turtles. The first breeding pair was observed in shore-based surveys on 14 September 2021 and the number of mating turtles then increased to a peak on 4 October, about 8 weeks before the peak in nesting. A total of 94 km of drone transects with associated video footage was analysed. In October, at the peak of the mating season, the ratio of adult turtles displaying breeding behaviours near the island was 0.51 female (95% CI ± 0.17), supporting previous conclusions that despite the female-biased (> 80%) hatchling sex ratio, this population likely has a fairly balanced OSR. These findings are likely explained by males breeding 2–3 times more frequently than females, which helps mitigate female-biased hatchling sex ratios. Assessing the OSR of populations with extreme female hatchling bias may help to inform whether intervention is needed to increase male hatchling production.

Single-species subgroups form within mixed-species shoals of tropical and temperate fishes - Kai C. Paijmans; David J. Booth; Marian YL. Wong (Environmental Biology of Fishes, 2022)

Habitat value of subsea wells and pipelines for fishery target species in Australia - Dianne McLean; Conrad W. Speed; Matthew Jon Birt; Jamie Colquhoun; Mark Case; Marcus Stowar; Todd Bond; Daniel Ierodiaconou; Sasha K. Whitmarsh; Michael D. Taylor; Sam Wines; David John Booth; et al. (Frontiers in Marine Science, 2022)
Subsea pipelines and wells installed to support the oil and gas industry represent some of the most extensive and numerous anthropogenic structures throughout global marine ecosystems. There remains a paucity of information on the habitat value of these structures for fishery target species and, as a result, little understanding of how decommissioning should be conducted to minimise impacts to populations of these economically and socially important species. We assess the diversity and abundance of species that are targets of recreational and commercial fisheries on 33 subsea wells and 17 pipelines across the tropical northwest and temperate southeast marine regions of Australia. We examine relationships between fish identity and abundance and a range of environmental (e.g., depth, location), infrastructure-specific (e.g., pipeline position, diameter, age, length of pipeline, height of well, position on well), and biological (% cover of epibiota) variables using video filmed by remotely operated vehicles during their routine offshore inspection and maintenance campaigns. A total of 100 fishery target species were observed across subsea well and pipeline infrastructure, 56 species uniquely observed on pipelines and nine unique to wells. The families Lutjanidae (snapper), Serranidae (rock cods, groupers, perch), and Carangidae (trevallies) were most common and abundant on both wells and pipelines. In the northwest, lutjanids were most abundant around the base of wells, in shallow depths, on shorter wells, and where pipelines spanned the seafloor. A greater number of fishery target species and abundance of ocean perch ( Helicolenus spp.) were also associated with pipelines that spanned the seafloor in temperate southeast Australia. The combined biomass of three species of snapper on wells in the northwest was 1,270 kg, with production levels for these species on each well estimated to be 105.2 g m 2 year -1 . The present study serves as an important reference point for informing decommissioning decisions for pipeline and well infrastructure and demonstrates the utility of industry-held data for science. We suggest that key predictor variables identified here be incorporated into comprehensive before-after-control-impact scientific studies for specific fields/assets to enable the prediction of potential impacts of decommissioning scenarios on marine communities present and quantification of such impacts after the decommissioning activity has occurred.

Foliar Nutrients Reflect Variation in Floristic Quality and Hydrology of Calcareous Fens - Arthur C. Ryzak; David Bart; Eric G. Booth; Steven P. Loheide (Wetlands, 2022)

Physiological factors facilitating the persistence of Pocillopora aliciae and Plesiastrea versipora in temperate reefs of south-eastern Australia under ocean warming - Raúl A. González-Pech; David J. Hughes; Paige Strudwick; Brett M. Lewis; David J. Booth; Will F. Figueira; Brigitte Sommer; David J. Suggett; Jennifer Matthews (Coral Reefs, 2022)
High-latitude reefs are suboptimal coral habitats, but such habitats are increasingly considered to be potential refugia from climate change for range-shifting coral reef species. Notably, tropical reef fish have been observed along the south-east coast of Australia, but their establishment on temperate rocky reefs is currently limited by winter minimum temperatures and other resource needs, such as structurally complex habitats typical of tropical reefs. Recent expansion of the branching subtropical coral Pocillopora aliciae in rocky reefs near Sydney (34° S) could diversify the architectural structure of temperate marine environments, thereby providing potential shelter for tropical reef taxa in warming seas. Here, we investigated whether future environmental conditions ( i.e. temperature increase) can influence the dominance of the subtropical branching coral P. aliciae over the resident encrusting coral Plesiastrea versipora in coastal Sydney by characterising physiological ( e.g. metabolic stability) and behavioural ( e.g. interspecific competitive hierarchy) traits that contribute to their competitive fitness. Our results suggest that a metabolic response, mediated by sterol and lipid metabolic pathways and provision of antioxidants, allows P. aliciae to reduce cellular stress and withstand exposure to short-term increased temperature. Conversely, P. versipora was more susceptible to heat exposure with no metabolic mediation observed. While P. versipora displayed greater aggressive behaviour when in direct contact with P. aliciae under all temperature conditions, the superior physiological and metabolic flexibility under increased temperatures of P. aliciae suggests that this species will likely outperform P. versipora under future increased temperatures. Such contrasting responses to environmental change would facilitate shifts in coral community and functional composition that could support further tropicalisation of coastal New South Wales.

Assessing the Effectiveness of Conservation Stocking for the Endangered White’s Seahorse Hippocampus whitei - David Harasti; Mitchell Brennan; David J. Booth (Frontiers in Marine Science, 2022)
The White’s seahorse Hippocampus whitei was listed as an Endangered species in 2020 on Australian state and federal legislation, as a result of population declines across its range attributed to habitat loss over the past decade. A captive-bred reintroduction program has been implemented as a possible management tool for species recovery, however, the viability of such a reintroduction program for seahorses has not been assessed to date. This study implemented a pilot captive-breeding program using adult H. whitei from Sydney Harbour, Australia, as brood stock. A total of 90 captive-bred seahorses were released into the wild on two different artificial habitat types (“seahorse hotels” and protective swimming net). Following release, a monthly post-release monitoring program was implemented for 12 months that involved underwater visual census surveys of the tagged seahorses. Sightings of captive-bred seahorse numbers were found to gradually decline over the 12-month period, with fewer seahorses found on the swimming net compared to the seahorse hotels and higher resighting probability of captive-bred animals on the seahorse hotels. After 12 months, 20% of the captive-bred seahorses were detected on the seahorse hotels, whilst two individuals were still observed 18 months after release on the hotels. Only 2% of captive-bred seahorses were observed on the swimming net after 12 months, with two individuals still detected on the net after two years. Nine of the captive-bred seahorses were found to reproduce in the wild, with two individuals observed mating with the wild population. This pilot study indicates that captive-bred seahorses can survive for up to two years in the wild, as well as contribute to local population recovery through reproductive success. However, while conservation stocking shows promise as a potential management tool to assist with threatened seahorse species recovery, there are several factors such as existing threats to the species that need to be addressed before such a program is implemented.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Recruiting a long way from home: Domino damselfish Dascyllus trimaculatus can detect new temperate coral habitat and conspecifics - Max J. O'Connell; Ashley M. Fowler; Sam J. Allan; Giglia A. Beretta; David J. Booth (Journal of Fish Biology, 2022)
Climate change is driving tropicalisation of temperate reefs, yet it is unclear how range‐shifting tropical fishes locate suitable habitat. The authors tested whether juvenile tropical damsels Dascyllus trimaculatus could detect rare coral habitat ( Pocillopora aliciae ) and conspecifics on temperate rocky reefs using olfactory and visual preference experiments. For all cues, individuals selected and spent more time than expected in aquarium areas with the cue present, which included coral odour and conspecific odour and visual cues. This indicates that vagrant coral‐reef fish can detect rare suitable habitat outside of their natal range.

Searching for seadragons: predicting micro‐habitat use for the common (weedy) seadragon ( Phyllopteryx taeniolatus ) based on habitat and prey - Sam J. Allan; Max J. O'Connell; David Harasti; O. Selma Klanten; David J. Booth (Journal of Fish Biology, 2022)
Habitat associations can be critical predictors of larger‐scale organism distributions and range shifts. Here the authors consider how a critical habitat, kelp ( Ecklonia radiata ) and prey (mysid crustacean swarms), can influence small‐ and large‐scale distribution on the iconic common (weedy) seadragon ( Phyllopteryx taeniolatus :Syngnathidae). P. taeniolatus are charismatic fish endemic to the temperate reefs of southern Australia, reported to range from Geraldton, Western Australia (28.7667°S, 114.6167°E) around southern Australia to Port Stephens, New South Wales (32.614369°S, 152.325676°E). The authors test a previously developed model of seadragon habitat preferences to predict P. taeniolatus occurrence within four sites from Sydney to the northern limit of their range in eastern Australia. They determined that P. taeniolatus associations with Ecklonia and mysid shrimp can be extrapolated across multiple sites to predict the occurrence of individual P. taeniolatus within a location/site. For instance, the authors demonstrated a significant positive relationship between the density of mysid swarms and the density of P. taeniolatus , evident across all sites despite large differences in the density of mysid swarms among sites. The findings are the first to model P. taeniolatus habitat associations across multiple sites to the northern limit of their range and have applications in protecting P. taeniolatus populations and how they may respond under climate change scenarios, such as poleward kelp retractions.

Phenotypic responses in fish behaviour narrow as climate ramps up - Almendra Rodriguez-Dominguez; Sean D. Connell; Ericka O. C. Coni; Minami Sasaki; David J. Booth; Ivan Nagelkerken (Climatic Change, 2022)
Natural selection alters the distribution of phenotypes as animals adjust their behaviour and physiology to environmental change. We have little understanding of the magnitude and direction of environmental filtering of phenotypes, and therefore how species might adapt to future climate, as trait selection under future conditions is challenging to study. Here, we test whether climate stressors drive shifts in the frequency distribution of behavioural and physiological phenotypic traits (17 fish species) at natural analogues of climate change (CO 2 vents and warming hotspots) and controlled laboratory analogues (mesocosms and aquaria). We discovered that fish from natural populations (4 out of 6 species) narrowed their phenotypic distribution towards behaviourally bolder individuals as oceans acidify, representing loss of shyer phenotypes. In contrast, ocean warming drove both a loss (2/11 species) and gain (2/11 species) of bolder phenotypes in natural and laboratory conditions. The phenotypic variance within populations was reduced at CO 2 vents and warming hotspots compared to control conditions, but this pattern was absent from laboratory systems. Fishes that experienced bolder behaviour generally showed increased densities in the wild. Yet, phenotypic alterations did not affect body condition, as all 17 species generally maintained their physiological homeostasis (measured across 5 different traits). Boldness is a highly heritable trait that is related to both loss (increased mortality risk) and gain (increased growth, reproduction) of fitness. Hence, climate conditions that mediate the relative occurrence of shy and bold phenotypes may reshape the strength of species interactions and consequently alter fish population and community dynamics in a future ocean.

Ocean warming and acidification degrade shoaling performance and lateralization of novel tropical–temperate fish shoals - Angus Mitchell; David J. Booth; Ivan Nagelkerken (Global Change Biology, 2022)
Gregarious behaviours are common in animals and provide various benefits such as food acquisition and protection against predators. Many gregarious tropical species are shifting poleward under current ocean warming, creating novel species and social interactions with local temperate taxa. However, how the dynamics of these novel shoals might be altered by future ocean warming and acidification remains untested. Here we evaluate how novel species interactions, ocean acidification and warming affect shoaling dynamics, motor lateralization and boldness of range‐extending tropical and co‐shoaling temperate fishes under controlled laboratory conditions. Fishes were exposed to 1 of 12 treatments (combinations of three temperature levels, two p CO 2 levels and two shoal type levels: mixed species or temperate only) for 38 days. Lateralization (a measure of asymmetric expression of cognitive function in group coordination and predator escape) of tropical and temperate species was right‐side biased under present‐day conditions, but side bias significantly diminished in tropical and temperate fishes under ocean acidification. Ocean acidification also decreased shoal cohesion irrespective of shoaling type, with mixed‐species shoals showing significantly lower cohesion than temperate‐only shoals irrespective of climate stressors. Tropical fish became bolder under ocean acidification (after 4 weeks), and temperate fish became bolder with increasing temperature, while ocean acidification dampened temperate fish boldness. Our findings highlight the direct effect of climate stressors on fish behaviour and the interplay with the indirect effects of novel species interactions. Because strong shoal cohesion and lateralization are key determinants of species fitness, their degradation under ocean warming and acidification could adversely affect species performance in novel assemblages in a future ocean, and might slow down tropical species range extensions.

Space use by the endemic common (weedy) seadragon ( Phyllopteryx taeniolatus ): influence of habitat and prey - Sam J. Allan; Max J. O'Connell; David Harasti; O. Selma Klanten; David J. Booth (Journal of Fish Biology, 2022)
The weedy seadragon ( Phyllopteryx taeniolatus : Syngnathidae) is an iconic fish endemic to the southern coastal waters of Australia. The authors of this study analysed the habitat preferences and factors influencing microhabitat selection by P. taeniolatus in a population from Kurnell, NSW, Australia. Using field surveys and the resource selection probability function, the authors determined that P. taeniolatus significantly preferred kelp ( Ecklonia radiata ) – dominated habitat and avoided rock‐dominated habitat. They showed P. taeniolatus preferred habitat of between 40% and 80% coverage of Ecklonia , while avoiding areas of P. taeniolatus habitat selection. The strong dependence of P. taeniolatus on Ecklonia habitat shown in this study was previously untested and highlights that reductions in Ecklonia cover under climate change, or impacts from increasing urbanisation, may render seadragon populations vulnerable to declines.

Land‐based measures to mitigate climate change: Potential and feasibility by country - Stephanie Roe; Charlotte Streck; Robert Beach; Jonah Busch; Melissa Chapman; Vassilis Daioglou; Andre Deppermann; Jonathan Doelman; Jeremy Emmet‐Booth; Jens Engelmann; Oliver Fricko; Chad Frischmann; et al. (Global Change Biology, 2021)
Land‐based climate mitigation measures have gained significant attention and importance in public and private sector climate policies. Building on previous studies, we refine and update the mitigation potentials for 20 land‐based measures in >200 countries and five regions, comparing “bottom‐up” sectoral estimates with integrated assessment models (IAMs). We also assess implementation feasibility at the country level. Cost‐effective (available up to $100/tCO 2 eq) land‐based mitigation is 8–13.8 GtCO 2 eq yr −1 between 2020 and 2050, with the bottom end of this range representing the IAM median and the upper end representing the sectoral estimate. The cost‐effective sectoral estimate is about 40% of available technical potential and is in line with achieving a 1.5°C pathway in 2050. Compared to technical potentials, cost‐effective estimates represent a more realistic and actionable target for policy. The cost‐effective potential is approximately 50% from forests and other ecosystems, 35% from agriculture, and 15% from demand‐side measures. The potential varies sixfold across the five regions assessed (0.75–4.8 GtCO2eq yr −1 ) and the top 15 countries account for about 60% of the global potential. Protection of forests and other ecosystems and demand‐side measures present particularly high mitigation efficiency, high provision of co‐benefits, and relatively lower costs. The feasibility assessment suggests that governance, economic investment, and socio‐cultural conditions influence the likelihood that land‐based mitigation potentials are realized. A substantial portion of potential (80%) is in developing countries and LDCs, where feasibility barriers are of greatest concern. Assisting countries to overcome barriers may result in significant quantities of near‐term, low‐cost mitigation while locally achieving important climate adaptation and development benefits. Opportunities among countries vary widely depending on types of land‐based measures available, their potential co‐benefits and risks, and their feasibility. Enhanced investments and country‐specific plans that accommodate this complexity are urgently needed to realize the large global potential from improved land stewardship.

Novel species interactions and environmental conditions reduce foraging competency at the temperate range edge of a range-extending coral reef fish - Ericka O. C. Coni; David J. Booth; Ivan Nagelkerken (Coral Reefs, 2021)

Long-term demographics of a coral-reef fish: growth, survival and abundance at several spatial scales - David J. Booth; Giglia A. Beretta (Coral Reefs, 2021)

A biallelic variant in CLRN2 causes non-syndromic hearing loss in humans - Barbara Vona; Neda Mazaheri; Sheng-Jia Lin; Lucy A. Dunbar; Reza Maroofian; Hela Azaiez; Kevin T. Booth; Sandrine Vitry; Aboulfazl Rad; Franz Rüschendorf; Pratishtha Varshney; Ben Fowler; et al. (Human Genetics, 2021)
Deafness, the most frequent sensory deficit in humans, is extremely heterogeneous with hundreds of genes involved. Clinical and genetic analyses of an extended consanguineous family with pre-lingual, moderate-to-profound autosomal recessive sensorineural hearing loss, allowed us to identify CLRN2, encoding a tetraspan protein, as a new deafness gene. Homozygosity mapping followed by exome sequencing identified a 14.96 Mb locus on chromosome 4p15.32p15.1 containing a likely pathogenic missense variant in CLRN2 (c.494C > A, NM_001079827.2) segregating with the disease. Using in vitro RNA splicing analysis, we show that the CLRN2 c.494C > A variant leads to two events: (1) the substitution of a highly conserved threonine (uncharged amino acid) to lysine (charged amino acid) at position 165, p.(Thr165Lys), and (2) aberrant splicing, with the retention of intron 2 resulting in a stop codon after 26 additional amino acids, p.(Gly146Lysfs*26). Expression studies and phenotyping of newly produced zebrafish and mouse models deficient for clarin 2 further confirm that clarin 2, expressed in the inner ear hair cells, is essential for normal organization and maintenance of the auditory hair bundles, and for hearing function. Together, our findings identify CLRN2 as a new deafness gene, which will impact future diagnosis and treatment for deaf patients.

A perturbed parameter ensemble of HadGEM3-GC3.05 coupled model projections: part 1: selecting the parameter combinations - David M. H. Sexton; Carol F. McSweeney; John W. Rostron; Kuniko Yamazaki; Ben B. B. Booth; James M. Murphy; Leighton Regayre; Jill S. Johnson; Ambarish V. Karmalkar (Climate Dynamics, 2021)

Natural and anthropogenic climate variability shape assemblages of range‐extending coral‐reef fishes - Cristián J. Monaco; David J. Booth; Will F. Figueira; Bronwyn M. Gillanders; David S. Schoeman; Corey J.A. Bradshaw; Ivan Nagelkerken (Journal of Biogeography, 2021)
Aim Climate change is redistributing species globally, resulting in altered community structures and ecosystem functioning. The current paradigm is that species should track temperature isoclines along latitudinal and depth gradients to remain within their thermal niches. However, the many exceptions to this rule point to complex ecological and environmental processes often overlooked in statistical models predicting species redistributions. We tested the contributions of natural versus anthropogenic climate change to the long‐term spatio‐temporal dynamics of assemblages of range‐shifting tropical fishes at the leading edge of redistribution fronts. Location East coast of Australia. Taxon Tropical coral‐reef fishes. Methods We analysed 16 years (2003–2018) of tropical species occurrences at two temperate locations using traditional diversity metrics (richness, accumulation curves and β ‐diversity). We also quantified the role of primary environmental covariates and estimated species associations using joint species distribution models. Results We reveal that tropical species richness has increased in this temperate ecosystem over time. Furthermore, we show that the richness of tropical vagrant species increased with the sea‐surface temperature experienced by both local vagrants and their putative source populations at the southern Great Barrier Reef, which accounted for 23.1% and 22.1% of the explained variance, respectively. We also detected a signal from El Niño‐Southern Oscillation, as species turnover and richness peaked during the strong La Niña event of 2010–2011. Main conclusions While the increases in ocean temperature and strength of the surface ocean current due to anthropogenic climate change are gradually favouring the poleward redistribution of tropical species, natural climatic oscillations can have a strong additive effect by rapidly modifying the pool of incoming species and potentially disrupting local communities.

Predicting Geographic Ranges of Marine Animal Populations Using Stable Isotopes: A Case Study of Great Hammerhead Sharks in Eastern Australia - Vincent Raoult; Clive N. Trueman; Kelsey M. Kingsbury; Bronwyn M. Gillanders; Matt K. Broadhurst; Jane E. Williamson; Ivan Nagelkerken; David J. Booth; Victor Peddemors; Lydie I. E. Couturier; Troy F. Gaston (Frontiers in Marine Science, 2020)
Determining the geographic range of widely dispersed or migratory marine organisms is notoriously difficult, often requiring considerable costs and typically extensive tagging or exploration programs. While these approaches are accurate and can reveal important information on the species, they are usually conducted on only a small number of individuals and can take years to produce relevant results, so alternative approaches may be preferable. The presence of latitudinal gradients in stable carbon isotope compositions of marine phytoplankton offers a means to quickly determine likely geographic population ranges of species that rely on productivity from these resources. Across sufficiently large spatial and temporal scales, the stable carbon isotopes of large coastal or pelagic marine species should reflect broad geographic patterns of resource use, and could be used to infer geographic ranges of marine populations. Using two methods, one based on a global mechanistic model and the other on targeted low-cost latitudinal sampling of fishes, we demonstrate and compare these stable isotope approaches to determine the core population geography of an apex predator, the great hammerhead ( Sphyrna mokarran ). Both methods indicated similar geographic ranges and suggested that S. mokarran recorded in south-eastern Australia are likely to be from more northern Australian waters. These approaches could be replicated in other areas where coastlines span predictable geographic gradients in isotope values and be used to determine the core population geography of highly mobile species to inform management decisions.

Impact of heavy rainfall events and shading on the temperature of sea turtle nests - Melissa N. Staines; David T. Booth; Christine A. Madden Hof; Graeme C. Hays (Marine Biology, 2020)

Dietary generalism accelerates arrival and persistence of coral‐reef fishes in their novel ranges under climate change - Cristián J. Monaco; Corey J. A. Bradshaw; David J. Booth; Bronwyn M. Gillanders; David S. Schoeman; Ivan Nagelkerken (Global Change Biology, 2020)
Climate change is redistributing marine and terrestrial species globally. Life‐history traits mediate the ability of species to cope with novel environmental conditions, and can be used to gauge the potential redistribution of taxa facing the challenges of a changing climate. However, it is unclear whether the same traits are important across different stages of range shifts (arrival, population increase, persistence). To test which life‐history traits most mediate the process of range extension, we used a 16‐year dataset of 35 range‐extending coral‐reef fish species and quantified the importance of various traits on the arrival time (earliness) and degree of persistence (prevalence and patchiness) at higher latitudes. We show that traits predisposing species to shift their range more rapidly (large body size, broad latitudinal range, long dispersal duration) did not drive the early stages of redistribution. Instead, we found that as diet breadth increased, the initial arrival and establishment (prevalence and patchiness) of climate migrant species in temperate locations occurred earlier. While the initial incursion of range‐shifting species depends on traits associated with dispersal potential, subsequent establishment hinges more on a species’ ability to exploit novel food resources locally. These results highlight that generalist species that can best adapt to novel food sources might be most successful in a future ocean.

Opposing climate-change impacts on poleward-shifting coral-reef fishes - David J. Booth (Coral Reefs, 2020)

Enhancing the Scientific Value of Industry Remotely Operated Vehicles (ROVs) in Our Oceans - Dianne L. McLean; Miles J. G. Parsons; Andrew R. Gates; Mark C. Benfield; Todd Bond; David J. Booth; Michael Bunce; Ashley M. Fowler; Euan S. Harvey; Peter I. Macreadie; Charitha B. Pattiaratchi; Sally Rouse; et al. (Frontiers in Marine Science, 2020)

Predation avoidance and foraging efficiency contribute to mixed‐species shoaling by tropical and temperate fishes - Kai C. Paijmans; David J. Booth; Marian Y. L. Wong (Journal of Fish Biology, 2020)
The formation of mixed‐species social groups, whereby heterospecifics form and maintain either transient or stable groups with each other, can confer substantial fitness benefits to individuals. Such benefits may arise via multiple mechanisms associated with both predation avoidance and foraging efficiency. In fishes, mixed‐species shoaling reportedly occurs where displaced tropical species (known as “vagrants”) interact with resident temperate species, although little is known about the nature and frequency of such interactions. To investigate this phenomenon, we used displaced tropical Indo‐pacific Sergeant Abudefduf vaigiensis settling in temperate south‐eastern Australia as a model system. Underwater visual surveys revealed shoal composition and size differed significantly between open‐water and reef habitats, with shoals in open habitats being larger and more speciose. Shoals containing A. vaigiensis were mainly mixed‐species, and larger and more speciose in open habitats than nearer to reef. Since both foraging efficiency (via access to plankton) and predation threat likely increase with increasing distance from reef habitat, we suggest that mixed‐species shoaling mitigates predation risk whilst allowing increased foraging opportunities for A. vaigiensis in open areas. These findings provide support for the importance of mixed‐species shoaling to the persistence of tropical reef fishes in temperate regions.

A Reconfigurable In Vitro Model for Studying the Blood–Brain Barrier - Monica L. Moya; Michael Triplett; Melinda Simon; Javier Alvarado; Ross Booth; Joanne Osburn; David Soscia; Fang Qian; Nicholas O. Fischer; Kristen Kulp; Elizabeth K. Wheeler (Annals of Biomedical Engineering, 2020)

Trophic niche segregation allows range‐extending coral reef fishes to co‐exist with temperate species under climate change - Kelsey M. Kingsbury; Bronwyn M. Gillanders; David J. Booth; Ivan Nagelkerken (Global Change Biology, 2020)
Changing climate is forcing many terrestrial and marine species to extend their ranges poleward to stay within the bounds of their thermal tolerances. However, when such species enter higher latitude ecosystems, they engage in novel interactions with local species, such as altered predator–prey dynamics and competition for food. Here, we evaluate the trophic overlap between range‐extending and local fish species along the east coast of temperate Australia, a hotspot for ocean warming and species range extensions. Stable isotope ratios (δ 15 N and δ 13 C) of muscle tissue and stomach content analysis were used to quantify overlap of trophic niche space between vagrant tropical and local temperate fish communities along a 730 km (6°) latitudinal gradient. Our study shows that in recipient temperate ecosystems, sympatric tropical and temperate species do not overlap significantly in their diet—even though they forage on broadly similar prey groups—and are therefore unlikely to compete for trophic niche space. The tropical and temperate species we studied, which are commonly found in shallow‐water coastal environments, exhibited moderately broad niche breadths and local‐scale dietary plasticity, indicating trophic generalism. We posit that because these species are generalists, they can co‐exist under current climate change, facilitating the existence of novel community structures.

Determining contemporary and historical sediment sources in a large drainage basin impacted by cumulative effects: the regulated Nechako River, British Columbia, Canada - David Gateuille; Philip N. Owens; Ellen L. Petticrew; Barry P. Booth; Todd D. French; Stephen J. Déry (Journal of Soils and Sediments, 2019)

Towards an ultimate explanation for mixed‐species shoaling - Kai C. Paijmans; David J. Booth; Marian Y. L. Wong (Fish and Fisheries, 2019)
The formation of social groups has important impacts on fitness for many animal species, with differences in group compositions resulting in a range of fitness outcomes for individuals. Recent interest in mixed‐species grouping, which extends from a large body of literature invested in understanding single‐species grouping, highlights novel complexities of group formation which relate to phenotypic, behavioural and physiological differences that naturally exist between species. Among fishes, mixed‐species shoaling is a common form of social grouping behaviour displayed across a range of marine and freshwater ecosystems. Research explaining mixed‐species shoaling shows some overlap with explanations for single‐species shoaling; however, it also demonstrates that distinct differences between species give rise to unique cost‐benefit trade‐offs which need to be incorporated into conceptual models of mixed‐species shoaling behaviour. Unique predation related trade‐offs may arise from inefficiency of the confusion effect, variation in vigilance between species and unequal species‐preferences shown by predators, whilst unique foraging‐related trade‐offs may arise from diet partitioning, variations in foraging behaviour and differences in competitive abilities between species. We review the literature on fitness outcomes associated with mixed‐species shoaling and present a new theoretical framework to explain the cost‐benefit trade‐offs for individuals within mixed‐species shoals. The framework incorporates both trade‐offs arising from differences between species and those arising from group size, the former having been largely ignored due to a focus on single‐species shoaling. Our framework is designed to inform future research striving to explain mixed‐species shoaling behaviour.

Finding plausible and diverse variants of a climate model. Part II: development and validation of methodology - Ambarish V. Karmalkar; David M. H. Sexton; James M. Murphy; Ben B. B. Booth; John W. Rostron; Doug J. McNeall (Climate Dynamics, 2019)

Can temperature-dependent predation rates regulate range expansion potential of tropical vagrant fishes? - Will F. Figueira; Belinda Curley; David J. Booth (Marine Biology, 2019)

Global Observing Needs in the Deep Ocean - Lisa A. Levin; Brian J. Bett; Andrew R. Gates; Patrick Heimbach; Bruce M. Howe; Felix Janssen; Andrea McCurdy; Henry A. Ruhl; Paul Snelgrove; Karen I. Stocks; David Bailey; Simone Baumann-Pickering; et al. (Frontiers in Marine Science, 2019)

Some Old Movies Become Classics – A Case Study Determining the Scientific Value of ROV Inspection Footage on a Platform on Australia’s North West Shelf - Paul G. Thomson; Ashley M. Fowler; Andrew R. Davis; Charitha B. Pattiaratchi; David J. Booth (Frontiers in Marine Science, 2018)

Coral expansion in Sydney and associated coral-reef fishes - David J. Booth; John Sear (Coral Reefs, 2018)

New poleward observations of 30 tropical reef fishes in temperate southeastern Australia - Ashley M. Fowler; Kerryn Parkinson; David J. Booth (Marine Biodiversity, 2018)

Temperature influences habitat preference of coral reef fishes: Will generalists become more specialised in a warming ocean? - Paloma A. Matis; Jennifer M. Donelson; Stephen Bush; Rebecca J. Fox; David J. Booth (Global Change Biology, 2018)
Climate change is expected to pose a significant risk to species that exhibit strong behavioural preferences for specific habitat types, with generalist species assumed to be less vulnerable. In this study, we conducted habitat choice experiments to determine how water temperature influences habitat preference for three common species of coral reef damselfish (Pomacentridae) that differ in their levels of habitat specialisation. The lemon damselfish Pomacentrus moluccensis , a habitat specialist, consistently selected complex coral habitat across all temperature treatments (selected based on local average seasonal temperatures naturally experienced in situ: ambient winter 22°C; ambient summer 28°C; and elevated 31°C). Unexpectedly, the neon damselfish Pomacentrus coelestis and scissortail sergeant Abudefduf sexfasciatus , both of which have more generalist habitat associations, developed strong habitat preferences (for complex coral and boulder habitat, respectively) at the elevated temperature treatment (31°C) compared to no single preferred habitat at 22°C or 28°C. The observed shifts in habitat preference with temperature suggest that we may be currently underestimating the vulnerability of some habitat generalists to climate change and highlight that the ongoing loss of complex live coral through coral bleaching could further exacerbate resource overlap and species competition in ways not currently considered in climate change models.

‘Stick with your own kind, or hang with the locals?’ Implications of shoaling strategy for tropical reef fish on a range‐expansion frontline - Shannen M. Smith; Rebecca J. Fox; David J. Booth; Jennifer M. Donelson (Global Change Biology, 2018)
Range shifts of tropical marine species to temperate latitudes are predicted to increase as a consequence of climate change. To date, the research focus on climate‐mediated range shifts has been predominately dealt with the physiological capacity of tropical species to cope with the thermal challenges imposed by temperate latitudes. Behavioural traits of individuals in the novel temperate environment have not previously been investigated, however, they are also likely to play a key role in determining the establishment success of individual species at the range‐expansion forefront. The aim of this study was to investigate the effect of shoaling strategy on the performance of juvenile tropical reef fishes that recruit annually to temperate waters off the south east coast of Australia. Specifically, we compared body‐size distributions and the seasonal decline in abundance through time of juvenile tropical fishes that shoaled with native temperate species (‘mixed’ shoals) to those that shoaled only with conspecifics (as would be the case in their tropical range). We found that shoaling with temperate native species benefitted juvenile tropical reef fishes, with individuals in ‘mixed’ shoals attaining larger body‐sizes over the season than those in ‘tropical‐only’ shoals. This benefit in terms of population body‐size distributions was accompanied by greater social cohesion of ‘mixed’ shoals across the season. Our results highlight the impact that sociality and behavioural plasticity are likely to play in determining the impact on native fish communities of climate‐induced range expansion of coral reef fishes.

Predicting Success of Range-Expanding Coral Reef Fish in Temperate Habitats Using Temperature-Abundance Relationships - David J. Booth; Giglia A. Beretta; Luke Brown; Will F. Figueira (Frontiers in Marine Science, 2018)

Time dependent pharmacokinetics of pembrolizumab in patients with solid tumor and its correlation with best overall response - Hongshan Li; Jingyu Yu; Chao Liu; Jiang Liu; Sriram Subramaniam; Hong Zhao; Gideon M. Blumenthal; David C. Turner; Claire Li; Malidi Ahamadi; Rik de Greef; Manash Chatterjee; et al. (Journal of Pharmacokinetics and Pharmacodynamics, 2017)

Microbial and Environmental Controls of Methane Fluxes Along a Soil Moisture Gradient in a Pacific Coastal Temperate Rainforest - Jesper Riis Christiansen; David Levy-Booth; Cindy E. Prescott; Sue J. Grayston (Ecosystems, 2016)

Response to “Comment on ‘Seagrass Viviparous Propagules as a Potential Long-Distance Dispersal Mechanism’ by A. C. G. Thomson et al” - Alexandra C. G. Thomson; Paul H. York; Tim M. Smith; Craig D. H. Sherman; David J. Booth; Michael J. Keough; D. Jeff Ross; Peter I. Macreadie (Estuaries and Coasts, 2016)

Temperate predators and seasonal water temperatures impact feeding of a range expanding tropical fish - Hayden J. Beck; David A. Feary; Ashley M. Fowler; Elizabeth M. P. Madin; David J. Booth (Marine Biology, 2016)

Bigger clutch sizes save offspring energy during nest escapes - Mohd Uzair Rusli; David T. Booth (Behavioral Ecology and Sociobiology, 2016)

Sediment pollution impacts sensory ability and performance of settling coral-reef fish - J. Jack O’Connor; David Lecchini; Hayden J. Beck; Gwenael Cadiou; Gael Lecellier; David J. Booth; Yohei Nakamura (Oecologia, 2016)

Behavioral Responses of a Tiny Insect, the Flower Thrips Frankliniella schultzei Trybom (Thysanoptera, Thripidae), to Atmospheric Pressure Change - Dylan J. McFarlane; Michelle A. Rafter; David T. Booth; Gimme H. Walter (Journal of Insect Behavior, 2015)

Reply to the Comment of Owen et al. on “Insulative capacity of the integument of the dugong (Dugong dugon): thermal conductivity, conductance and resistance measured by in vitro heat flux” by Horgan, Booth, Nichols and Lanyon (2014) - Janet M. Lanyon; Patrick Horgan; David Booth; Cassandra Nichols (Marine Biology, 2015)

Seagrass Viviparous Propagules as a Potential Long-Distance Dispersal Mechanism - Alexandra C. G. Thomson; Paul H. York; Timothy M. Smith; Craig D. H. Sherman; David J. Booth; Michael J. Keough; D. Jeff Ross; Peter I. Macreadie (Estuaries and Coasts, 2015)

Stable isotope relationships between mothers, eggs and hatchlings in loggerhead sea turtles Caretta caretta - Alice S. Carpentier; David T. Booth; Karen E. Arthur; Colin J. Limpus (Marine Biology, 2015)

There’s no smell like home: how sensory ontogeny plays a role in the early life history of estuarine-dependent fishes - O'Connor J.; Booth David; Swearer Steve; Fielder Stewart; Leis Jeffrey (Frontiers in Marine Science, 2015)

Resolving issues with environmental impact assessment of marine renewable energy installations - Ilya M. D. Maclean; Richard Inger; David Benson; Cormac G. Booth; Clare B. Embling; W. James Grecian; Johanna J. Heymans; Kate E. Plummer; Michael Shackshaft; Carol E. Sparling; Ben Wilson; Lucy J. Wright; et al. (Frontiers in Marine Science, 2014)

Lithium carbonate in the management of cannabis withdrawal: a randomized placebo-controlled trial in an inpatient setting - Jennifer Johnston; Nicholas Lintzeris; David J. Allsop; Anastasia Suraev; Jessica Booth; Dean S. Carson; David Helliwell; Adam Winstock; Iain S. McGregor (Psychopharmacology, 2014)

Latitudinal shifts in coral reef fishes: why some species do and others do not shift - David A Feary; Morgan S Pratchett; Micheal J Emslie; Ashley M Fowler; Will F Figueira; Osmar J Luiz; Yohei Nakamura; David J Booth (Fish and Fisheries, 2014)
Climate change is resulting in rapid poleward shifts in the geographical distribution of many tropical fish species, but it is equally apparent that some fishes are failing to exhibit expected shifts in their geographical distribution. There is still little understanding of the species‐specific traits that may constrain or promote successful establishment of populations in temperate regions. We review the factors likely to affect population establishment, including larval supply, settlement and post‐settlement processes. In addition, we conduct meta‐analyses on existing and new data to examine relationships between species‐specific traits and vagrancy. We show that tropical vagrant species are more likely to originate from high‐latitude populations, while at the demographic level, tropical fish species with large body size, high swimming ability, large size at settlement and pelagic spawning behaviour are more likely to show successful settlement into temperate habitats. We also show that both habitat and food limitation at settlement and within juvenile stages may constrain tropical vagrant communities to those species with medium to low reliance on coral resources.

Transient climate changes in a perturbed parameter ensemble of emissions-driven earth system model simulations - James M. Murphy; Ben B. B. Booth; Chris A. Boulton; Robin T. Clark; Glen R. Harris; Jason A. Lowe; David M. H. Sexton (Climate Dynamics, 2014)

Insulative capacity of the integument of the dugong (Dugong dugon): thermal conductivity, conductance and resistance measured by in vitro heat flux - Patrick Horgan; David Booth; Cassandra Nichols; Janet M. Lanyon (Marine Biology, 2014)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Interactions between perturbations to different Earth system components simulated by a fully-coupled climate model - F. Hugo Lambert; Glen R. Harris; Matthew Collins; James M. Murphy; David M. H. Sexton; Ben B. B. Booth (Climate Dynamics, 2013)

Probabilistic projections of transient climate change - Glen R. Harris; David M. H. Sexton; Ben B. B. Booth; Mat Collins; James M. Murphy (Climate Dynamics, 2013)

Nest and maternal origin can influence morphology and locomotor performance of hatchling green turtles (Chelonia mydas) incubated in field nests - David T. Booth; Róisín Feeney; Yui Shibata (Marine Biology, 2013)

Climate model errors, feedbacks and forcings: a comparison of perturbed physics and multi-model ensembles - Matthew Collins; Ben B. B. Booth; B. Bhaskaran; Glen R. Harris; James M. Murphy; David M. H. Sexton; Mark J. Webb (Climate Dynamics, 2011)

Precipitation extremes and the impacts of climate change on stormwater infrastructure in Washington State - Eric A. Rosenberg; Patrick W. Keys; Derek B. Booth; David Hartley; Jeff Burkey; Anne C. Steinemann; Dennis P. Lettenmaier (Climatic Change, 2010)

UK 1-D regional velocity models by analysis of variance of P-wave travel times from local earthquakes - David C. Booth (Journal of Seismology, 2010)

Increasing ocean temperatures allow tropical fishes to survive overwinter in temperate waters - WILL F. FIGUEIRA; DAVID J. BOOTH (Global Change Biology, 2010)
The southeast coast of Australia is a global hotspot for increasing ocean temperatures due to climate change. The temperate incursion of the East Australian Current (EAC) is increasing, affording increased connectivity with the Great Barrier Reef. The survival of tropically sourced juveniles over the winter is a significant stumbling block to poleward range shifts of marine organisms in this region. Here we examine the dependence of overwintering on winter severity and prewinter recruitment for eight species of juvenile coral reef fishes which are carried into temperate SE Australia (30–37 °S) by the EAC during the austral summer. The probability of persistence was most strongly influenced by average winter temperature and there was no effect of recruitment strength. Long‐term (138 years) data indicate that winter water temperatures throughout this region are increasing at a rate above the global average and predictions indicate a further warming of >2 °C by the end of the century. Rising ocean temperatures are resulting in a higher frequency of winter temperatures above survival thresholds. Current warming trajectories predict 100% of winters will be survivable by at least five of the study species as far south as Sydney (34 °S) by 2080. The implications for range expansions of these and other species of coral reef fish are discussed.

Extreme boldness precedes starvation mortality in six-lined trumpeter (Pelates sexlineatus) - Peter A. Biro; David J. Booth (Hydrobiologia, 2009)

The effects of incubation temperature on the morphology and composition of Australian Brush-turkey (Alectura lathami) chicks - Yvonne A. Eiby; David T. Booth (Journal of Comparative Physiology B, 2009)

Ontogeny of space use and diet of two temperate damselfish species, Parma microlepis and Parma unifasciata - Emily C. Buckle; David J. Booth (Marine Biology, 2009)

Locomotion performance of green turtle hatchlings from the Heron Island Rookery, Great Barrier Reef - Tahia Ischer; Katarina Ireland; David Terrington Booth (Marine Biology, 2009)

Preface - José Badal; David Booth; Martha Savage; Zhongjie Zhang (Journal of Seismology, 2009)

Size–frequency dynamics of NE Pacific abyssal ophiuroids (Echinodermata: Ophiuroidea) - J. Ashley T. Booth; Henry A. Ruhl; Lawrence L. Lovell; David M. Bailey; Kenneth L. Smith (Marine Biology, 2008)

Selective mortality of a coral reef damselfish: role of predator–competitor synergisms - Will F. Figueira; David J. Booth; Marcus A. Gregson (Oecologia, 2008)

Sand and nest temperatures and an estimate of hatchling sex ratio from the Heron Island green turtle (Chelonia mydas) rookery, Southern Great Barrier Reef - David T. Booth; Candida Freeman (Coral Reefs, 2006)

Ratio-dependent response of a temperate Australian estuarine system to sustained nitrogen loading - Melanie J. Bishop; Brendan P. Kelaher; Marcus P. Lincoln Smith; Paul H. York; David J. Booth (Oecologia, 2006)

Swimming performance of hatchling green turtles is affected by incubation temperature - Elizabeth A. Burgess; David T. Booth; Janet M. Lanyon (Coral Reefs, 2006)

Towards quantifying uncertainty in transient climate change - Matthew Collins; Ben B. B. Booth; Glen R. Harris; James M. Murphy; David M. H. Sexton; Mark J. Webb (Climate Dynamics, 2006)

Genome-wide SNP discovery and linkage analysis in barley based on genes responsive to abiotic stress - Nils Rostoks; Sharon Mudie; Linda Cardle; Joanne Russell; Luke Ramsay; Allan Booth; Jan T. Svensson; Steve I. Wanamaker; Harkamal Walia; Edmundo M. Rodriguez; Peter E. Hedley; Hui Liu; et al. (Molecular Genetics and Genomics, 2005)

Estuarine habitat preferences of Anguilla australis and A. reinhardtii glass eels as inferred from laboratory experiments - Veronica Silberschneider; Bruce C. Pease; David J. Booth (Environmental Biology of Fishes, 2004)

Influence of recruit condition on food competition and predation risk in a coral reef fish - David J. Booth; Giglia A. Beretta (Oecologia, 2004)

Movement, Home Range and Site Fidelity of the Weedy Seadragon Phyllopteryx taeniolatus (Teleostei: Syngnathidae) - Jaime Sanchez-Camara; David J. Booth (Environmental Biology of Fishes, 2004)

Density- and size-dependent mortality of a settling coral-reef damselfish ( Pomacentrus moluccensis Bleeker) - Benjamin J. Brunton; David J. Booth (Oecologia, 2003)

Effects of enhanced nitrogen deposition and phosphorus limitation on nitrogen budgets of semi‐natural grasslands - Gareth K. Phoenix; Rosemary E. Booth; Jonathan R. Leake; David J. Read; J. Philip Grime; John A. Lee (Global Change Biology, 2003)
Increased reactive atmospheric N deposition has been implicated in floristic changes in species‐rich acidic and calcareous grasslands, but the fate of this pollutant N in these ecosystems is unknown. This paper reports the first analysis of N budgets and N fluxes for two grasslands in the White Peak area of Derbyshire, one of the most heavily N‐polluted locations in the UK. N fluxes were monitored in lysimeter cores (retaining the original turfs) taken from field plots of unimproved acidic and calcareous grasslands that had received (in addition to ambient N deposition) simulated enhanced N deposition treatments of 3.5 and 14 g N m −2 yr −1 for 6 years. The influence of reducing phosphorus limitation was assessed by factorial additions of P. Seasonal leached losses of nitrate, ammonia and organic N were monitored in detail along with estimates of N removal through simulated grazing and gaseous losses through denitrification and volatilization. The rates of N fluxes by these pathways were used to create N budgets for the grasslands. Both grasslands were found to be accumulating much of the simulated additional N deposition: up to 89% accumulated in the calcareous grassland and up to 38% accumulated in the acidic grassland. The major fluxes of N loss from these grasslands were by simulated grazing and leaching of soluble organic N (constituting 90% of leached N under ambient conditions). Leached inorganic N (mainly nitrate) contributed significantly to the output flux of N under the highest N treatment only. Loss of N through ammonia volatilization accounted for less than 6% of the N added as simulated deposition, while denitrification contributed significantly to output fluxes only in the acidic grassland during winter. The implications of the results for ecosystem N balances and the likely consequences of N accumulation on these grasslands are discussed.

Settlement and Density of Juvenile Fish Assemblages in Natural, Zostera Capricorni (Zosteraceae) and Artificial Seagrass Beds - Judy Upston; David J. Booth (Environmental Biology of Fishes, 2003)

Fundamental changes in light scattering associated with infection of marine bacteria by bacteriophage - William M. Balch; James M. Jr Vaughn; James F. Novotny; David T. Drapeau; Joaquim I. Goes; Emily Booth; Janeen M. Lapierre; Cathy L. Vining; Amanda Ashe; James M. Jr Vaughn (Limnology and Oceanography, 2002)
Bacteria and phytoplankton are key determinants of the ocean's inherent optical properties. Despite their high abundance, marine viruses have generally been thought to play a minor role in ocean optics because of their small scattering cross‐sections. Nevertheless, the role of specific viral infection on the optical properties of bacteria and phytoplankton has remained unknown (i.e., as viruses disrupt micron‐sized host cells to produce submicron cell debris). Here, we used laboratory and mesocosm cultures of marine bacteria for virus infection experiments in which growth conditions and host‐virus specificity were controlled. We report that the chief optical impact of viruses is associated with infection and lysis of their hosts. We quantitatively describe, for the first time, two optical changes associated with infection and lysis of marine bacteria by bacteriophage: (1) rapid, strong shifts in the magnitude and shape of the optical volume scattering function and (2) rapid production of colored dissolved organic material. Qualitatively, these changes result in nearly complete clearing of turbid host bacterial suspensions. Although some optical differences would be expected between infection of bacteria in laboratory cultures versus field populations (mainly because of differences in cell size), these results are applicable to the field, especially for dense host suspensions such as in blooms. Even in nonbloom situations, as long as the host bacteria contribute a significant amount of the total particle backscattering, we expect that virus‐induced backscattering changes would be detectable by use of satellite or aircraft remote‐sensing techniques.

Resource use by Enneapterygius Rufopileus and Other Rockpool Fishes - Veronica Silberschneider; David J. Booth (Environmental Biology of Fishes, 2001)

Water treatment control using the joint estimation outlier detection method - Christine Wright; David Booth (Environmental Modeling & Assessment, 2001)

Using PERT methodology in nuclear material safeguards and chemical process control - David E. Booth; Thomas L. Isenhour (Environmental Modeling & Assessment, 2000)

Studies on the dermal and systemic bioavailability of polycyclic aromatic compounds in high viscosity oil products - David Potter; Ewan D. Booth; Henk C. A. Brandt; Robert W. Loose; Robert A. J. Priston; Alan S. Wright; William P. Watson (Archives of Toxicology, 1999)

β-chemokine expression and distribution in paraffin-embedded transplant renal biopsy sections: analysis by scanning laser confocal microscopy - H. Robertson; Janice Wheeler; Adrian R. Morley; Trevor A. Booth; David Talbot; John A. Kirby (Histochemistry and Cell Biology, 1998)

Toxicity, accumulation, and elimination of polycyclic aromatic sulfur heterocycles inDaphnia magna - David A. Eastmond; Gary M. Booth; Milton L. Lee (Archives of Environmental Contamination and Toxicology, 1984)